Parental Management on Juvenile Delinquency through Low Self-control And Misperception. Issue 4 (3rd April 2023) - Baek, Hyunin; Posadas, Carlos E.; Kwak, Dae-Hoon
ABSTRACT: Delinquent behaviors among juveniles have been problematic in South Korea. More specifically, the recent rate of juvenile crimes has increased. Despite efforts to find causes of juvenile delinquency, it has remained an unresolved social problem in South Korea. Concerning these issues, this study applies Gottfredson and Hirschi's low self-control and Akers's definitions to the relationship between parenting and juvenile delinquency. This study used a Korean data set from the International Self-Report Delinquency 3 Study (n = 1, 469). Through Structural Equation Modeling, this study found that low self-control and misperception about delinquency fully mediated the relationship between parental management and juvenile delinquency. Further, low self-control was statistically related to misperceptions about deviant behaviors. Overall, findings revealed that parenting played a critical role in demonstrating the relationship between low self-control, misperception, and juvenile delinquency. Therefore, the integrated model would provide a potential solution for juvenile delinquency in South Korea.